Cellular and molecular events on the development of mammalian thyroid C cells. Issue 3 (8th January 2016) - Kameda, Yoko
Abstract : Thyroid C cells synthesize and secrete calcitonin, a serum calcium‐lowering hormone. This review provides our current understanding of mammalian thyroid C cells from the molecular and morphological perspectives. Several transcription factors and signaling molecules involved in the development of C cells have been identified, and genes expressed in the pharyngeal pouch endoderm, neural crest‐derived mesenchyme in the pharyngeal arches, and ultimobranchial body play critical roles for the development of C cells. It has been generally accepted, without much‐supporting evidence, that mammalian C cells, as well as the avian cells, are derived from the neural crest. However, by fate mapping of neural crest cells in both Wnt1‐Cre/R26R and Connexin(Cxn)43‐lacZ transgenic mice, we showed that neural crest cells colonize neither the fourth pharyngeal pouch nor the ultimobranchial body. E‐cadherin, an epithelial cell marker, is expressed in thyroid C cells and their precursors, the fourth pharyngeal pouch and ultimobranchial body. Furthermore, E‐cadherin is colocalized with calcitonin in C cells. Recently, lineage tracing in Sox17‐2A‐iCre/R26R mice has clarified that the pharyngeal endoderm‐derived cells give rise to C cells. Together, these findings indicate that mouse thyroid C cells are endodermal in origin. Developmental Dynamics 245:323–341, 2016 . © 2015 Wiley Periodicals, Inc. Key Findings: The morphogenesis of thyroid C cells is achieved via a multi‐step process; formation of the fourth pharyngeal pouch, budding of ultimobranchial body (UB) from the fourth pharyngeal pouch, fusion of UB with thyroid primordium, and differentiation of UB cells into C cells. Transcription factors and signaling molecules involved in the development of thyroid C cells were described. Lineage tracing studies using several kinds of transgenic mice have indicated that mouse thyroid C cells are endodermal in origin.